You should remeber that you may convert the polar coordinates into rectangular coordinates using the following formulas such that:

`sin theta = y/r => y = r sin theta`

`cos theta = x/r => x = r cos theta`

`x^2 + y^2 = r^2`

The problem provides the information that...

## See

This Answer NowStart your **subscription** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You should remeber that you may convert the polar coordinates into rectangular coordinates using the following formulas such that:

`sin theta = y/r => y = r sin theta`

`cos theta = x/r => x = r cos theta`

`x^2 + y^2 = r^2`

The problem provides the information that `r = - 4 sin theta` , hence, multiplying by r both sides yields:

`r^2 = -4r sin theta => r^2 = -4y`

Substituting `x^2 + y^2` for `r^2` yields:

`x^2 + y^2 = -4y`

You should move `-4y` to the left side such that:

`x^2 + y^2 + 4y = 0`

You need to complete the square `y^2 + 4y` adding 4 both sides such that:

`x^2 + y^2 + 4y + 4 = 4`

You need to convert the expansion `y^2 + 4y + 4` into t he square of binomial such that:

`x^2 + (y+2)^2 = 4`

**Hence, converting the polar form of equation into the rectangular form yields `x^2 + (y+2)^2 = 4,` thus you need to select the answer D.**